Efficacy of normalization of vaginal microbiota after antimicrobial treatment for bacterial vaginosis and bacterial vaginosis in pregnant women (results of the multicenter prospective non-interventional comparative study) - V.E. Radzinskiy; I.M. Ordiyants; E.V. Tikhomirova; I.V. Sakhautdinova; E.M. Zulkarneeva (LCC «Medicine-Inform», 2021)
V.E. Radzinskiy1, I.B. Manukhin2, I.M. Ordiyants1, V.E. Balan3, E.V. Tikhomirova3, I.V. Sakhautdinova4, E.M. Zulkarneeva4 1Russian University of Peoples' Friendship, Moscow, Russian Federation 2A.I. Yevdokimov Moscow State University of Medicine and Dentistry, Moscow,  Russian Federation 3Moscow Regional Research Institute of Obstetrics & Gynecology, Moscow,  Russian Federation 4Bashkir State Medical University, Ufa, Russian Federation Aim: to assess the efficacy and safety of Lactogynal® to normalize vaginal microflora after antimicrobial treatment for bacterial vaginosis (BV) and to prevent recurrences of vulvovaginal candidiasis (VVC) during pregnancy. Patients and Methods: this multicenter prospective non-interventional comparative study included 100 women in the 3rd trimester of pregnancy diagnosed with acute BV (n=50) or acute VVC (n=50). 25 women of each group received standard antimicrobial treatment only. 25 women of each group received Lactogynal® as the second step of antimicrobial treatment. Women were followed up until delivery and discharge. The rate of BV and VVC recurrences before delivery was considered the key indicator of treatment efficacy. In addition, obstetrical and perinatal outcomes, compliance, the type and duration of antimicrobial treatment for BV and VVC were evaluated. Results: in women with BV and VVC who received Lactogynal®, no recurrences during the follow-up were reported (p<0.05). In women who received standard antimicrobial treatment only, the rate of recurrences of BV and VVC was 40% and 28%, respectively. As to the complications of pregnancy, delivery, and the postpartum period, women with BV who received probiotic therapy were less often diagnosed with anemia (p<0.05) while women with VVC who received probiotic therapy were less often diagnosed with the premature rupture of membranes (p<0.05). Conclusions: Lactogynal® is an effective and safe tool to normalize vaginal microflora after antimicrobial treatment for BV and to prevent VVC recurrences during the 3rd trimester of pregnancy. This drug (as a part of complex treatment for BV and VVC) reduces the risk of recurrences and promotes a more favorable pregnancy course until delivery. Keywords: lactobacilli, bacterial vaginosis, vulvovaginal candidiasis, pregnancy, vaginal microflora. For citation: Radzinskiy V.E., Manukhin I.B., Ordiyants I.M. et al. Efficacy of normalization of vaginal microbiota after antimicrobial treatment for bacterial vaginosis and bacterial vaginosis in pregnant women (results of the multicenter prospective non-interventional comparative study). Russian Journal of Woman and Child Health. 2021;4(3):192-200 (in Russ.). DOI: 10.32364/2618-8430-2021-4-3-192-200.